Participation of religious in the mission of Christ according to the Code of Canon Law of 1983 - Szewczul, Bożena (Prawo Kanoniczne, 2024)
The author of the article shows some aspects of including religious in the saving mission of Christ - aspects mentioned by the Church legislator in the Code of Canon Law of 1983. These include: consecration of life through the implementation of the evangelical counsels, fraternal life in the community on model of the community of Apostles, monastic cloister, involvement in the mission in accordance with the charisma of the institute founder, the need for fidelity in maintaining the mission of the institute and its apostolic works related, care for religious formation as preparation for mission. Continuing Christ's mission and bringing it to its fullness depends largely on faithfulness religious in imitating Christ in his dedication to the Father. The religious themselves then become a place of Christ's presence and an extension of his life in history. Their total devotion of life to God not only enables deeper participation in the mission of Christ, but also gives the opportunity to become a Father’s mission, just as Christ was. Thus, religious can remind other believers that not life has a mission, but that it itself is a mission.